A Rare Case Report of Neonatal Neurofibromatosis Type 1 Presented with Giant Faciocervical Mass and Complicated with HIE - Liu B; Wang W; Bi J; Huo R (International Medical Case Reports Journal, 2023)
Boce Liu,1 Wenjing Wang,1 Jianhai Bi,2 Ran Huo1,2 1Department of Plastic Surgery, Shandong Provincial Hospital, Shandong University, Jinan, People’s Republic of China; 2Department of Plastic Surgery, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, People’s Republic of ChinaCorrespondence: Ran Huo, Department of Plastic Surgery, Shandong Provincial Hospital, Shandong University, Jinan, Shandong, People’s Republic of China, Tel +86-15168889001, Fax +86-0531-68778153, Email huoran@medmail.com.cnAbstract: A newborn with giant faciocervical mass and presented with asphyxia during birth was admitted to the hospital. After stabilizing her vital sign, we provided the patient with image examinations and whole-exome sequencing, which revealed a heterozygous variation of neurofibromatosis type 1 (NF1). The final diagnosis of the patient was NF1 complicated with neonatal hypoxic-ischemic encephalopathy (NHIE). During hospitalization, the patient received comprehensive and systematic care. There was no reports of similar cases in the literature. So, this report aimed to elucidate the special clinical manifestations, diagnosis, treatment and prognosis of NF1 complicated with NHIE by analyzing the clinical data of the patient and her family and reviewing relevant literature.Keywords: neurofibromatosis type 1, neonatal hypoxic-ischemic encephalopathy, NF1 gene variation, whole-exome sequencing